Resection of pancreatic and splenic metastases from alveolar soft part sarcoma: a case report - Satoshi Arakawa; Yukio Asano; Norihiko Kawabe; Hidetoshi Nagata; Yuka Kondo; Shinpei Furuta; Masahiro Shimura; Chihiro Hayashi; Takayuki Ochi; Kenshiro Kamio; Toki Kawai; Hironobu Yasuoka; et al. (Surgical Case Reports)
Abstract Background We present a case of pancreatic and splenic metastases following alveolar soft part sarcoma (ASPS), which was successfully treated by surgery. Case presentation A 41-year-old male was referred to our hospital in 2012. Computed tomography (CT) showed the presence of a pancreatic tumor. In 2002, the patient had undergone surgical resection of an ASPS of the anal region. In 2009, during follow-up, CT revealed lung metastases, which prompted surgical resection of the lung, followed by resection of the head skin in 2011. Abdominal ultrasonography (US) revealed the presence of isodense masses sized 34 mm in the pancreatic head and 60 mm within the spleen. The contrast-enhanced US revealed a solitary lesion with enhancement. Contrast-enhanced CT revealed solitary lesions with enhancement within the pancreatic head, spleen, and liver. The patient underwent metastasectomies from the pancreas, spleen, and liver. The patient was discharged on postoperative day 22 without recurrence for 18 months after metastasectomy. Twelve years after primary resection and 2 years after metastasectomy, the patient died as a consequence of multiple metastases. Conclusions We have presented a rare case of pancreatic and spleen metastases from ASPS. Resection by radical metastasectomy was successful without morbidity. Thus, for improved survival of patients with multiple metastases from ASPS, metastasectomy may be indicated. If multiple metastases are resectable, surgical approaches may be the preferred treatment.